2014
DOI: 10.3390/biology3020403
|View full text |Cite
|
Sign up to set email alerts
|

Causes and Consequences of Age-Related Changes in DNA Methylation: A Role for ROS?

Abstract: Recent genome-wide analysis of C-phosphate-G (CpG) sites has shown that the DNA methylome changes with increasing age, giving rise to genome-wide hypomethylation with site‑specific incidences of hypermethylation. This notion has received a lot of attention, as it potentially explains why aged organisms generally have a higher risk of age-related diseases. However, very little is known about the mechanisms that could cause the occurrence of these changes. Moreover, there does not appear to be a clear link betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 140 publications
(203 reference statements)
0
28
0
Order By: Relevance
“…Previous studies have established that there is a decrease in global DNA methylation with age, 2527 but this relationship has not been established in HF. The age-related changes in healthy adults are likely not relevant in chronic HF.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous studies have established that there is a decrease in global DNA methylation with age, 2527 but this relationship has not been established in HF. The age-related changes in healthy adults are likely not relevant in chronic HF.…”
Section: Discussionmentioning
confidence: 96%
“…Global methylation studies show varying DNA methylation with age, 2527 exercise, 28,29 diet, 3032 and environmental factors. 3335 While NLRP3 and caspase-1 have inflammatory functions independent of the inflammasome, ASC functions only as an adapter protein as part of the inflammasome; the level of CpG methylation of ASC may control inflammasome formation.…”
Section: Introductionmentioning
confidence: 99%
“…50 Under physiological conditions, ROS are present in every cell, being produced by the mitochondrial and cytoplasmic oxidation processes. A low to moderate ROS concentration is essential to maintain normal physiological processes.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…46 In addition, Mohammadipour et al 47 observed reduced hippocampal cell proliferation and decreased spatial memory, inhibitory memory, and learning ability in rat offspring after the maternal administration of TiO 2 NPs during pregnancy. In that study, rats were exposed to 100 mg/kg body weight of TiO 2 NPs every day, which is equivalent to ~6,000 mg/60 kg of body weight for humans, far lower than the LD 50 (dose required to kill 50% of a population of test animals) of TiO 2 for rats (12,000 mg/kg body weight) per the 1969 guidelines of the World Health Organization (WHO). Although this dose was less than the dose reported by the WHO, it still had side effects on the hippocampus.…”
mentioning
confidence: 99%
“…A molecular study suggested that oxidative stress and ROS can impair the process of DNA methylation by inhibiting substrate synthesis or decreasing the activity of epigenetic enzymes such as DNMT and HDAC [2831]. It is unclear if ROS can impair the histone-to-protamine transition in a similar manner and further investigation is thus warranted.…”
Section: Discussionmentioning
confidence: 99%